Identity of the teacher-researcher in collaborative action research: concerns reflected in a research journal (2012)
In this paper I report the insights of my personal research journal as part of a collaborative action research project I facilitated in a secondary school where I teach English as a foreign language. I kept a journal so as to offer the natural history of my research towards my doctoral degree. In this project I worked together with four participating teachers but I assumed a complex identity as I was a teacher-researcher i.e. doctoral researcher and a teacher. This entailed different roles and interests which generated opportunities and tensions. Qualitative analysis of my journal reveals complex concerns at different levels which signal the individual struggles of a teacher-researcher involved in collaboration.En este artículo presento un reporte de mis reflexiones sobre mi diario de investigación, que usé como parte de un proyecto de investigación-acción colaborativo que propicié en una escuela secundaria donde enseño inglés como lengua extranjera. Llevé un diario con miras a ofrecer la historia natural de mi proyecto de doctorado. En este proyecto trabajé junto a otros cuatro docentes participantes y asumí una identidad compleja ya que fui docente investigador y docente participante. Esto implicó diferentes roles e intereses que generaron tanto experiencias positivas como tensiones con mis colegas. El análisis cualitativo de mi diario revela preocupaciones complejas en diferentes niveles y señala las luchas individuales del docente investigador involucrado en colaboración.